2D Materials: Large‐Size 2D β‐Cu2S Nanosheets with Giant Phase Transition Temperature Lowering (120 K) Synthesized by a Novel Method of Super‐Cooling Chemical‐Vapor‐Deposition (Adv. Mater. 37/2016). Issue 37 (4th October 2016) - Li, Bo; Huang, Le; Zhao, Guangyao; Wei, Zhongming; Dong, Huanli; Hu, Wenping; Wang, Lin‐Wang; Li, Jingbo
Abstract : On page 8271, Z. Wei, W. Hu, L.‐W. Wang, J. Li and co‐workers describe 2D β‐Cu2 S nanosheets with movable Cu and fixed S atoms that exist at around room temperature, where the Cu atoms can be fixed to form γ‐Cu2 S at lower temperatures. In the back cover image, a series of temperatures are represented by fire and ice. The background exhibits the potential applications of phase transitions in 2D Cu2 S, such as information storage and nanoelectronics.